Re-reading the myth of medusa in ecological crisis - Muhammad Fuad Hasyim (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This paper reinterprets the myth of Medusa in the context of ecological crisis. By exploring the relationship between myth, the unconscious, the oppression of women, and nature, this paper attempts to reveal how hierarchical structures of domination shape the human perspective in understanding nature as an object. Methods: This study adopts a qualitative interpretative approach using symbolic hermeneutics grounded in Carl Jung’s concept of the collective unconscious and Hélène Cixous’ feminist deconstruction. Jung’s framework is used to read Medusa as an archetypal symbol of repressed fear and human–nature relations, while Cixous’ perspective critically reinterprets the myth to expose patriarchal narratives and reconstruct Medusa as a metaphor for liberation and ecological consciousness. Findings: This paper asserts that the root of the oppression and exploitation of nature lies in the binary logic that separates humans and nature. The human narrative of nature is also a narrative of domination, in which the distance between humans and nature is constantly maintained. Humans construct the